Influence of Sewage Sludge and Nitrogen Fertilization on Growth, Nutrient Content and Heavy Metal Uptake by Rice Straw - Kabir, MK; Ullah, SM; Jahan, S; Ullah, M Bashir; Kamal, ATMM (Bangladesh Journal of Scientific and Industrial Research, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> A pot experiment was conducted to study the effects of sewage sludge and nitrogen fertilization on the growth, yield, nutrient and heavy metal uptake into rice straw (Oriza setiva L cv. BRRI dhan-36). There were five 5 treatments (T0, T1, T2, T3 and T4) consisting of 5 levels of sewage sludge (0, 60, 120, 200 and 300 t/ha) and 5 levels of nitrogen (280, 49, 35, 28 and 21 kg/ha). In the experiment the highest height of the rice plant (97.33 cm per plant) and number (55.00) of tillers per four plants were recorded with the treatment, 300 t/ha sewage sludge plus 21 kg/ha nitrogen. The length of spikelet was significantly high in all treatments compared to the treatment, 300 t/ha sewage sludge plus 21 kg/ha nitrogen. On the other hand, both the fresh and dry weight of rice straw was significantly high in the aforesaid treatment compared to the other treatments. The contents of N, K, Na, Ca, Mg, Fe, Cu, Zn and Pb in rice straw increased significantly with increasing sewage sludge levels and were observed high at the treatment, 300 t/ha sewage sludge plus 21 kg/ha nitrogen, but the amount of P and Mn uptake decreased significantly with increasing sewage sludge levels showing an antagonistic effect. Cr, Cd and Ni contents were below detectable level. Key words: Sewage sludge, Fertilization, Rice straw, Nutrient, Heavy metal Â  doi: 10.3329/bjsir.v43i4.2248 Bangladesh J. Sci. Ind. Res. 43(4), 571-580, 2008